KARAKTERISTIK MORFOLOGI KALUS LAMTORO (Leucaena leucocephala CV TARRAMBA) TERADAPTASI pH 3.4 HASIL IRADIASI SINAR GAMMA 40Gy BERDASARKAN PERBEDAAN SUMBER SITOKININ (KINETIN, BAP, TDZ) PADA KULTUR JARINGAN - Prihantoro I; Anandia A.; Aryanto A. T.; Karti P. D. M. H. (Udayana University, 2019)
Lamtoro, a legume tree plant with high protein content that has a wide range of environmental adaptation to dry stress, but relatively limited to acid stress. Mutation of lamtoro through 40 Gy gamma ray irradiation on callus culture produces lamtoro callus candidates adapted with pH 3.4. Aim of the study was to measure the morphological characteristics of adapted lamtoro cv Tarramba pH 3.4 that produced by 40Gy gamma ray irradiation based on differences of cytokinins in tissue culture. The study used complete randomized design with three treatments of different sources of cytokines i.e. kinetin, BAP and TDZ with 10 replications. The results showed that 0.5 ppm TDZ was the best treatment in callus diameter, and produced crumbly callus texture, but showed callus color response that tended to be light green.